Nanometer porous silicon carbon negative electrode material and preparation method and application thereof
By sintering nano-scale Mg2Si in a carbon dioxide atmosphere and pickling to form a porous structure, the problem of high temperature required for the preparation of nano-scale porous silicon carbon anode materials in the prior art is solved, and the effect of preparing high-performance nano-porous silicon carbon anode materials at a lower temperature is achieved.
Patent Information
- Application Number
- CN202411820512.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art requires a high sintering temperature when preparing nano-scale porous silicon carbon anode materials, resulting in high manufacturing costs and difficult to control process parameters.
Nano-scale Mg2Si is sintered in a carbon dioxide atmosphere, with a sintering temperature not exceeding 550°C, and a porous structure is formed by pickling to obtain a nanoporous silicon-carbon negative electrode material with a particle size of less than 150 nm.
Preparing nanoporous silicon carbon anode material at a lower temperature reduces the preparation cost and process control difficulty, effectively suppresses volume expansion during the cycle, and improves the conductivity of the material.
Smart Images

Figure BDA0005182995140000131
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary batteries and relates to a negative electrode material, in particular to a nanoporous silicon-carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] The theoretical specific capacity of silicon-based negative electrode materials is 4200mAh / g, which is higher than the theoretical specific capacity of natural graphite and artificial graphite. However, silicon will produce a volume change of about 300% during the process of lithium insertion and removal, which can easily cause the silicon electrode to become powdery and peel off, making its cycle stability very poor.
[0003] Methods to solve the cycle stability problem of silicon-based negative electrode materials include silicon nano-sizing, carbon coating, ceramic layer coating, improved binder and electrolyte additives, with carbon coating being the most commonly used method. At the same time, nano-sizing or making silicon porous, shortening the diffusion distance and alleviating volume expansion are the keys to improving the performance of silicon-carbon negative electrode materials.
[0004] The preparation process of silicon-carbon negative electrode materials involves multiple steps such as the preparation of nano-silicon powder, compounding of carbon materials, sintering, etc. Each step requires precise control of process parameters, otherwise the performance of the final nano-porous silicon-carbon negative electrode material will be affected; however, the existing technology requires higher temperatures when preparing nano-scale porous silicon-carbon negative electrode materials, which not only leads to higher manufacturing costs, but also increases the difficulty of controlling process parameters.
[0005] Therefore, it is necessary to provide a method for preparing nanoporous silicon-carbon negative electrode materials at a relatively low temperature. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a nanoporous silicon-carbon negative electrode material and a preparation method and application thereof. The preparation method can obtain a nanoporous silicon-carbon negative electrode material with a particle size of less than 150 nm at a relatively low sintering temperature, thereby reducing the preparation cost and the difficulty of process control.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a nanoporous silicon-carbon negative electrode material, the preparation method comprising the following steps:
[0009] Sintering nano-sized Mg2Si in a carbon dioxide atmosphere, and acid-washing the sintered product to obtain the nano-porous silicon-carbon negative electrode material;
[0010] The sintering temperature is ≤550°C.
[0011] The preparation method provided by the present invention can obtain a nanoporous silicon-carbon negative electrode material with a particle size of less than 150 nm under the condition that the sintering temperature does not exceed 550° C. by using nano-scale magnesium silicide, thereby reducing the preparation cost and the difficulty of process control. The nanoporous silicon-carbon negative electrode material obtained by the preparation method can effectively suppress the volume expansion during the cycle, and is not easy to break, pulverize and fall off from the negative electrode current collector. Moreover, the nanostructure is conducive to the embedding and extraction of ions, thereby improving the conductivity of the nanoporous silicon-carbon negative electrode material.
[0012] Preferably, the particle size of the nano-scale Mg2Si is less than 50 nm.
[0013] Preferably, the median particle size D50 of the nano-sized Mg2Si is 20 nm-50 nm.
[0014] Preferably, the preparation method of the nano-sized Mg2Si comprises: using cyclohexane as a ball milling medium to ball mill micron-sized Mg2Si to obtain the nano-sized Mg2Si.
[0015] Preferably, the ball-to-material ratio of the ball mill is 10:1 to 40:1.
[0016] Preferably, the rotation speed of the ball mill is 100 r / min to 500 r / min.
[0017] Preferably, the ball milling time is more than 48 hours.
[0018] Preferably, the heating rate of the sintering is 1.5°C / min to 2.5°C / min.
[0019] Preferably, the sintering time is 1.6 h to 2.4 h.
[0020] Preferably, the acid used for pickling includes hydrochloric acid and / or hydrofluoric acid.
[0021] Preferably, the preparation method comprises the following steps:
[0022] (1) using cyclohexane as a ball milling medium, ball milling micron-sized Mg2Si at a rotation speed of 100 r / min to 500 r / min and a ball-to-material ratio of 10:1 to 40:1 to obtain nano-sized Mg2Si with a particle size of less than 50 nm;
[0023] (2) introducing carbon dioxide gas into a tubular furnace, heating the temperature to a sintering temperature at a heating rate of 1.5° C. / min to 2.5° C. / min, sintering nano-Mg2Si for a sintering time of 1.6 h to 2.4 h, and cooling the furnace to obtain a sintered product;
[0024] (3) acid-washing the sintered product to form a porous structure; filtering and purifying to obtain a nano-scale porous silicon-carbon negative electrode material.
[0025] In a second aspect, the present invention provides a nanoporous silicon-carbon negative electrode material, wherein the nanoporous silicon-carbon negative electrode material is obtained by the preparation method described in the first aspect.
[0026] The particle size of the nanoporous silicon-carbon negative electrode material is less than 150nm and the specific surface area is 20m 2 / g-40m 2 / g.
[0027] In a third aspect, the present invention provides an electrochemical device, which includes the nanoporous silicon-carbon negative electrode material prepared by the preparation method described in the first aspect, or includes the nanoporous silicon-carbon negative electrode material described in the second aspect.
[0028] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The preparation method provided by the present invention uses nano-scale magnesium silicide, and can obtain a nanoporous silicon-carbon negative electrode material with a particle size of less than 150nm under the condition that the sintering temperature does not exceed 550°C, thereby reducing the preparation cost and the difficulty of process control; and the nanoporous silicon-carbon negative electrode material obtained by the preparation method can effectively inhibit the volume expansion during the cycle process, and at the same time, it is not easy to break, pulverize and fall off from the negative electrode current collector, and the nanostructured structure is conducive to the embedding and removal of ions, thereby improving the conductivity of the nanoporous silicon-carbon negative electrode material. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0032] A certain embodiment of the present invention provides a method for preparing a nanoporous silicon-carbon negative electrode material, the preparation method comprising the following steps:
[0033] Sintering nano-sized Mg2Si in a carbon dioxide atmosphere, and acid-washing the sintered product to obtain the nano-porous silicon-carbon negative electrode material;
[0034] The sintering temperature is ≤550°C.
[0035] The preparation method provided by the present invention can obtain a nanoporous silicon-carbon negative electrode material with a particle size of less than 150 nm under the condition that the sintering temperature does not exceed 550° C. by using nano-scale magnesium silicide, thereby reducing the preparation cost and the difficulty of process control. The nanoporous silicon-carbon negative electrode material obtained by the preparation method can effectively suppress the volume expansion during the cycle, and is not easy to break, pulverize and fall off from the negative electrode current collector. Moreover, the nanostructure is conducive to the embedding and extraction of ions, thereby improving the conductivity of the nanoporous silicon-carbon negative electrode material.
[0036] In the preparation method provided by the present invention, the required sintering temperature does not exceed 550°C, for example, it can be 500°C, 510°C, 520°C, 530°C, 540°C or 550°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] In some embodiments, the particle size of the nano-scale Mg2Si is less than 50 nm, for example, it can be 10 nm, 20 nm, 30 nm, 40 nm or 49 nm, but is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0038] In the present invention, the particle size of nano-sized Mg2Si is less than 50 nm, which means that the maximum particle size of nano-sized Mg2Si is less than 50 nm.
[0039] In some embodiments, the median particle size D50 of the nano-sized Mg2Si is 20 nm-50 nm, for example, 20 nm, 30 nm, 40 nm or 50 nm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0040] In some embodiments, the method for preparing the nano-sized Mg2Si comprises: using cyclohexane as a ball milling medium to ball mill micron-sized Mg2Si to obtain the nano-sized Mg2Si.
[0041] In some embodiments, the median particle size D50 of the micron-sized Mg2Si is 5 μm-20 μm, for example, 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm or 20 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] In some embodiments, the ball-to-material ratio of the ball mill is 10:1 to 40:1, for example, it can be 10:1, 15:1, 20:1, 25:1, 30:1, 35:1 or 40:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] In some embodiments, the ball mill has a rotation speed of 100 r / min to 500 r / min, for example, 100 r / min, 200 r / min, 300 r / min, 400 r / min or 500 r / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0044] In certain embodiments, the ball milling time is more than 48 hours.
[0045] The longer the ball milling time, the smaller the particle size of the nano-Mg2Si obtained in theory, but too long ball milling time will reduce the preparation efficiency and increase the preparation cost; therefore, controlling the appropriate ball milling time can obtain the desired nano-Mg2Si at a suitable cost.
[0046] In certain embodiments, the ball milling is performed in a high energy ball mill.
[0047] In some embodiments, the sintering heating rate is 1.5°C / min to 2.5°C / min, for example, it can be 1.5°C / min, 1.8°C / min, 2°C / min, 2.2°C / min or 2.5°C / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] In some embodiments, the sintering time is 1.6 h to 2.4 h, for example, 1.6 h, 1.8 h, 2 h, 2.2 h or 2.4 h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0049] In certain embodiments, the acid used for pickling includes hydrochloric acid and / or hydrofluoric acid.
[0050] The present invention does not specifically limit the concentration of hydrochloric acid and / or hydrofluoric acid. In the present invention, the composition of the sintered product includes a silicon-carbon composite material and MgO. Hydrochloric acid and / or hydrofluoric acid can react with MgO and incompletely reacted Mg2Si to generate MgCl2. After removing impurities, a nanoporous silicon-carbon negative electrode material is finally obtained.
[0051] In certain embodiments, the preparation method comprises the following steps:
[0052] (1) using cyclohexane as a ball milling medium, ball milling micron-sized Mg2Si at a rotation speed of 100 r / min to 500 r / min and a ball-to-material ratio of 10:1 to 40:1 to obtain nano-sized Mg2Si with a particle size of less than 50 nm;
[0053] (2) introducing carbon dioxide gas into a tubular furnace, heating the temperature to a sintering temperature at a heating rate of 1.5° C. / min to 2.5° C. / min, sintering nano-Mg2Si for a sintering time of 1.6 h to 2.4 h, and cooling the furnace to obtain a sintered product;
[0054] (3) acid-washing the sintered product to form a porous structure; filtering and purifying to obtain a nano-scale porous silicon-carbon negative electrode material.
[0055] A certain embodiment of the present invention provides a nanoporous silicon-carbon negative electrode material, and the nanoporous silicon-carbon negative electrode material is obtained by the preparation method described in any embodiment.
[0056] The particle size of the nanoporous silicon-carbon negative electrode material is less than 150nm and the specific surface area is 20m 2 / g-40m 2 / g.
[0057] A certain embodiment of the present invention provides an electrochemical device, which includes the nanoporous silicon-carbon negative electrode material prepared by the preparation method described in any embodiment, or includes the nanoporous silicon-carbon negative electrode material described in any embodiment.
[0058] The electrochemical device comprises a positive electrode, a negative electrode, a separator and an electrolyte.
[0059] In some embodiments, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the surface of the negative electrode current collector; the negative electrode active material layer includes a nanoporous silicon-carbon negative electrode material.
[0060] In certain embodiments, the negative electrode current collector includes any one of copper foil, aluminum foil, stainless steel foil, titanium foil, nickel foam, copper foam, and a polymer substrate coated with a conductive metal, or a combination of at least two thereof.
[0061] In some embodiments, the negative electrode active material layer further includes a binder, and the binder includes any one of polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, polyvinyl fluoride, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyethylene, polypropylene or epoxy resin, or a combination of at least two thereof.
[0062] In some embodiments, the negative electrode active material layer further includes a conductive agent, and the conductive agent includes any one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, copper, nickel, aluminum or silver, or a combination of at least two thereof.
[0063] In some embodiments, the preparation method of the negative electrode includes: mixing and dispersing nanoporous silicon-carbon negative electrode material, conductive agent, binder and optional additives in a solvent, stirring evenly, uniformly coating on the negative electrode current collector, and drying to obtain a negative electrode containing a negative electrode active material layer.
[0064] In certain embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector.
[0065] In some embodiments, the positive electrode active material layer includes a positive electrode material, and the positive electrode material includes any one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium iron manganese phosphate, lithium vanadium phosphate, lithium vanadium phosphate, lithium iron phosphate, lithium titanate or a lithium-rich manganese-based material, or a combination of at least two thereof.
[0066] In certain embodiments, the positive electrode active material includes a positive electrode binder and a positive electrode conductor.
[0067] Optionally, the positive electrode binder includes any one of polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, polyvinyl fluoride, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyethylene, polypropylene, styrene-butadiene rubber or epoxy resin, or a combination of at least two thereof.
[0068] Optionally, the positive electrode conductive agent includes any one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, copper, nickel, aluminum or silver, or a combination of at least two thereof.
[0069] In some embodiments, the preparation method of the positive electrode includes: uniformly mixing a positive electrode material, a positive electrode conductive agent and a positive electrode binder in a solvent, and then coating the mixture on a positive electrode current collector.
[0070] In certain embodiments, the separator includes a substrate layer and a surface treatment layer.
[0071] Optionally, the substrate layer is a non-woven fabric, a film or a composite film with a porous structure, and the material includes any one of polyethylene, polypropylene, polyethylene terephthalate or polyimide, or a combination of at least two thereof.
[0072] In some embodiments, a surface treatment layer is disposed on at least one surface of the substrate layer, and the material of the surface treatment layer includes polymer and / or inorganic substance.
[0073] The inorganic material includes inorganic particles and a binder, wherein the inorganic particles include any one or a combination of at least two of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The binder includes any one or a combination of at least two of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxy, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene.
[0074] The polymer material includes any one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyvinylalkane, polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene) or a combination of at least two thereof.
[0075] In certain embodiments, the electrolyte includes lithium hexafluorophosphate.
[0076] In certain embodiments, the electrolyte further comprises any one of fluoroether, fluoroethylene carbonate or ether nitrile, or a combination of at least two thereof.
[0077] In certain embodiments, the electrolyte further includes a lithium salt including lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate.
[0078] In some embodiments, the electrolyte further includes an organic solvent and a sodium salt, the organic solvent includes any one of EC, PC, DMC, DEC, EMC, EA, FEC or VC or a combination of at least two thereof; the sodium salt includes any one of NaClO4, NaPF6, NaBF4, NaFSI or NaTFSI or a combination of at least two thereof.
[0079] Example 1
[0080] This embodiment provides a method for preparing a nanoporous silicon-carbon negative electrode material, comprising the following steps:
[0081] (1) Using cyclohexane as the ball milling medium, milling micron-sized Mg2Si (particle size D50 is 10 μm) for 48 h at a speed of 200 r / min and a ball-to-material ratio of 20:1 to obtain nano-sized Mg2Si (particle size D50 is 30 nm);
[0082] (2) introducing carbon dioxide gas into a tubular furnace, heating the temperature to a sintering temperature of 550° C. at a heating rate of 2° C. / min, sintering nano-Mg2Si for 2 h, and cooling the furnace to obtain a sintered product;
[0083] (3) washing the sintered product with hydrochloric acid to form a porous structure; and filtering and purifying to obtain a nano-scale porous silicon-carbon negative electrode material.
[0084] Example 2
[0085] This embodiment provides a method for preparing a nanoporous silicon-carbon negative electrode material, comprising the following steps:
[0086] (1) Using cyclohexane as the ball milling medium, milling micron-sized Mg2Si (particle size D50 is 15 μm) for 48 h at a speed of 100 r / min and a ball-to-material ratio of 10:1 to obtain nano-sized Mg2Si (particle size D50 is 35 nm);
[0087] (2) introducing carbon dioxide gas into a tubular furnace, heating the temperature to a sintering temperature of 550° C. at a heating rate of 1.5° C. / min, sintering nano-Mg2Si for 2.4 h, and cooling the furnace to obtain a sintered product;
[0088] (3) washing the sintered product with hydrochloric acid to form a porous structure; and filtering and purifying to obtain a nano-scale porous silicon-carbon negative electrode material.
[0089] Example 3
[0090] This embodiment provides a method for preparing a nanoporous silicon-carbon negative electrode material, comprising the following steps:
[0091] (1) Using cyclohexane as the ball milling medium, milling micron-sized Mg2Si (particle size D50: 20 μm) for 48 h at a speed of 500 r / min and a ball-to-material ratio of 40:1 to obtain nano-sized Mg2Si (particle size D50: 45 nm);
[0092] (2) introducing carbon dioxide gas into a tubular furnace, heating the temperature to a sintering temperature of 550° C. at a heating rate of 2.5° C. / min, sintering nano-Mg2Si for 1.6 h, and cooling the furnace to obtain a sintered product;
[0093] (3) washing the sintered product with hydrochloric acid to form a porous structure; and filtering and purifying to obtain a nano-scale porous silicon-carbon negative electrode material.
[0094] Example 4
[0095] This embodiment provides a method for preparing a nanoporous silicon-carbon negative electrode material, which is the same as that of Embodiment 1 except that the sintering temperature is 530°C.
[0096] Example 5
[0097] This embodiment provides a method for preparing a nanoporous silicon-carbon negative electrode material, which is the same as that of Embodiment 1 except that the sintering temperature is 500°C.
[0098] Example 6
[0099] This embodiment provides a method for preparing a nanoporous silicon-carbon negative electrode material, which is the same as that of Embodiment 1 except that the ball milling time is changed to make the particle size D50 of the nano-Mg2Si be 60 nm.
[0100] Comparative Example 1
[0101] This comparative example provides a method for preparing a porous silicon-carbon negative electrode material, comprising the following steps:
[0102] (1) introducing carbon dioxide gas into a tubular furnace, heating the temperature to 550° C. at a heating rate of 2° C. / min, sintering the micron-sized Mg2Si in Example 1 for 2 h, and cooling the furnace to obtain a sintered product;
[0103] (2) washing the sintered product with hydrochloric acid to form a porous structure; and filtering and purifying to obtain a nano-scale porous silicon-carbon negative electrode material.
[0104] Performance Testing
[0105] The negative electrode materials obtained in the above examples and comparative examples were used to prepare lithium-ion batteries, and the electrochemical performance was tested:
[0106] Positive electrode: LiCoO2, conductive carbon black and polyvinylidene fluoride (PVDF) were added to N-methylpyrrolidone in a mass ratio of 95:2.5:2.5 to obtain a positive electrode slurry, and then the positive electrode slurry was coated on an aluminum foil, and the positive electrode was obtained after drying and cold pressing.
[0107] Negative electrode: nanoporous silicon-carbon negative electrode material, conductive carbon black, Super P and binder polyacrylic acid (PAA) are mixed in a mass ratio of 70:15:5:10 to obtain a negative electrode slurry, and the obtained negative electrode slurry is coated on a copper foil, dried, and cold pressed to obtain a negative electrode.
[0108] Electrolyte: In a dry argon environment, propylene carbonate, ethylene carbonate, and diethyl carbonate were mixed in a weight ratio of 1:1:1, LiPF6 was added to a concentration of 1.15 mol / L, and then fluoroethylene carbonate was added to a weight percentage of 12.5%.
[0109] Separator: Polyethylene with a porosity of 35% was used as the separator.
[0110] The positive electrode, separator and negative electrode are stacked in order and wound to obtain a bare cell. The bare cell is then placed in a casing and injected with electrolyte for packaging. After formation, degassing and trimming, a lithium-ion battery is obtained.
[0111] Cyclic performance test: At 25°C, charge to 4.4V at 0.7C constant current, charge to 0.025C at constant voltage, let stand for 5 minutes, discharge to 3V at 0.5C to get the initial capacity. Perform a 0.7C charge and 0.5C discharge cycle test, and terminate after 200 cycles. The capacity retention rate results are shown in Table 1.
[0112] Expansion rate test: Use a screw micrometer to test the initial thickness when half charged (50% SOC). When the battery is fully charged (100% SOC) after 200 cycles, use a screw micrometer to test the thickness of the battery at this time. The ratio of the thickness to the initial thickness is the expansion rate. The results are shown in Table 1.
[0113] Table 1
[0114]
[0115] In summary, the preparation method provided by the present invention can obtain a nanoporous silicon-carbon negative electrode material with a particle size of less than 150 nm under the condition that the sintering temperature does not exceed 550°C by using nano-scale magnesium silicide, thereby reducing the preparation cost and the difficulty of process control; and the nanoporous silicon-carbon negative electrode material obtained by the preparation method can effectively inhibit the volume expansion during the cycle, and at the same time, it is not easy to break, powderize and fall off from the negative electrode current collector, and the nanostructured structure is conducive to the embedding and removal of ions, thereby improving the conductivity of the nanoporous silicon-carbon negative electrode material.
[0116] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a nanoporous silicon-carbon negative electrode material, characterized in that: The preparation method comprises the following steps: Sintering nano-sized Mg2Si in a carbon dioxide atmosphere, and acid-washing the sintered product to obtain the nano-porous silicon-carbon negative electrode material; The sintering temperature is ≤550°C.
2. The preparation method according to claim 1, characterized in that: The particle size of the nano-scale Mg2Si is less than 50 nm.
3. The preparation method according to claim 2, characterized in that: The median particle size D50 of the nano-sized Mg2Si is 20nm-50nm.
4. The preparation method according to claim 2 or 3, characterized in that: The preparation method of the nano-sized Mg2Si comprises: using cyclohexane as a ball milling medium, and ball milling micron-sized Mg2Si by a high-energy ball mill to obtain the nano-sized Mg2Si.
5. The preparation method according to claim 4, characterized in that: The ball-to-material ratio of the ball mill is 10:1 to 40:1; And / or, the rotation speed of the ball mill is 100 r / min to 500 r / min; And / or, the ball milling time is more than 48 hours.
6. The preparation method according to claim 1, characterized in that: The heating rate of the sintering is 1.5°C / min to 2.5°C / min; And / or, the sintering time is 1.6h to 2.4h.
7. The preparation method according to claim 1, characterized in that: The acid used for pickling includes hydrochloric acid and / or hydrofluoric acid.
8. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: (1) using cyclohexane as a ball milling medium, ball milling micron-sized Mg2Si at a rotation speed of 100 r / min to 500 r / min and a ball-to-material ratio of 10:1 to 40:1 to obtain nano-sized Mg2Si with a particle size of less than 50 nm; (2) introducing carbon dioxide gas into a tubular furnace, heating the temperature to a sintering temperature at a heating rate of 1.5° C. / min to 2.5° C. / min, sintering nano-Mg2Si for a sintering time of 1.6 h to 2.4 h, and cooling the furnace to obtain a sintered product; (3) acid-washing the sintered product to form a porous structure; filtering and purifying to obtain a nano-scale porous silicon-carbon negative electrode material.
9. A nanoporous silicon-carbon negative electrode material, characterized in that: The nanoporous silicon-carbon negative electrode material is obtained by the preparation method according to any one of claims 1 to 8; The particle size of the nanoporous silicon-carbon negative electrode material is less than 150nm and the specific surface area is 20m 2 / g-40m 2 / g.
10. An electrochemical device, characterized in that: The electrochemical device comprises the nanoporous silicon-carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 8, or comprises the nanoporous silicon-carbon negative electrode material according to claim 9.